eko asked in Science & MathematicsMathematics · 1 decade ago

Is (x-1)(x+2)(x+3) a factor of (x3+6x2+3x-10)?

please explain why... thank you

2 Answers

Relevance
  • DOVE
    Lv 6
    1 decade ago
    Favorite Answer

    x3+6x2+3x-10

    x=1

    1+6+3-10=0

    TRUE

    So x-1 is factor of x3+6x2+3x-10

    x=-2

    -8+24-6-10= 0

    TRUE

    So x+2 is also factor x3+6x2+3x-10

    x=3

    -27+ 54 -9-10 is not zero

    So x+3 is not factor of x3+6x2+3x-10

    So (x-1)(x+2)(x+3) as a whole is not factor of x3+6x2+3x-10

  • 1 decade ago

    (x-1)(x+2) is a factor but since x+3 is not than the triple product is not a factor of the given expression.

    When the expression is evaluated for x = -3

    -27 + 24 -9 - 10 = -22 For x + 3 to be a factor the evaluation would have to be zero.

    Source(s): Retired math teacher
Still have questions? Get your answers by asking now.